When local power meets hydropower: Reconceptualizing resettlement along the Nam Gnouang River in Laos - Katus, S; Suhardiman, Diana; Senaratna Sellamuttu, Sonali (Elsevier, 2016)
In Laos, hydropower development is occurring at rapid, though controversial pace. While hydropower development could in principle contribute to the country’s development objectives to promote economic growth and reduce poverty, it also impacts people’s livelihoods especially local communities living along the river. Focusing on the transition of Nam Gnouang River into a reservoir, this article looks at the process of resettlement of four neighboring villages in Bolikhamxai Province, Laos into one resettlement site, Ban Keosengkham. Conceptualizing hydropower development as a ‘technology’ of power, it illustrates how power relations between villagers, local government authorities, and dam developers determine resettlement processes and outcomes.